Truth and other lies: online foreign image management in Iran during the Rouhani Era - Fellner, Elena (2024)
Abstract: States’ communication with foreign audiences is commonly conceptualized as either propaganda (by autocracies), public diplomacy (by democracies), or PR work (by public relations agencies). This article argues that strict separation between these areas of foreign policy communication hinders more than helps our understanding of how states attempt to garner support among a global audience. Theorizing Iran’s ex-foreign minister Mohammad Javad Zarif’s communication on Twitter as a fusion of PR, public diplomacy, and propaganda with emotionally evocative performances of nationalism, this article shows how foreign policy communication develops in tandem with, but also in contrast to audience reactions and discussions